Kinetic Modelling of Solid-Liquid Extraction of Anthocyanins of Gynura Crepioides Leaves - Mei Lin, Wong; Zainal Abidin, Zurina (International Journal of Engineering and Technology, 2019)
Gynura crepioides is one of the natural resources of flavonoid compounds, including anthocyanins (ACs) that provide a lot of nutritional values to human and use as a natural colourant. For efficient extraction, optimization and kinetic data is very essential. In this investigation, optimization and kinetic modelling focusing on temperature effect on solid-liquid extraction of freeze-dried anthocyanins leaves of Gynura crepioides was performed. Freeze drying material was used in extraction to ensure high recovery of useful bioactive compounds in subsequent process. It was found that the rate of extraction was very fast at the beginning, but it began to slow down until it remained constant and reached the plateau after 45 minutes for all temperatures. As temperature increases, the initial extraction rate (h) and extraction rate constant (k) values also increased. The highest initial extraction rate and extraction rate constant were calculated to be 16.64 mg L-1 min-1 and 17.8 x 10-3 L mg-1 min-1 at 333K.However, after 60 minutes of extraction time, degradation of anthocyanins can be seen at 333K and thus reduce the yield. Higher temperature is known to reduce the quantity and quality of bioactive compound. Hence temperature of lower than 333K is desirable for industrial application. The kinetics of extraction data were corresponding well to second-order reaction. The activation energy is calculated as 18.45 kJ mol-1, which is an indication of an endothermic process. An empirical correlation was also done to establish the relationship of extraction rate constant and initial extraction rate with respect to temperature. Both parameters were found to increase with increase temperature. Finally, a three-dimensional model was predicted to show the capacity of extraction at all times and temperatures of extraction. This predicted model exhibited good fitting to experimental values with low standard deviation.Â Â Â